ASSESSMENT OF INDICES OF VEHICLE SERVICE STATIONS IN CHERKASY CITY - О. А. Тригуб; А. П. Солтус; Д. В. Рудь (Вісник Черкаського державного технологічного університету, 2018)
Modern market conditions, which are characterized by increasing of competition strictness, create preconditions for maximizing the proximity of service center services to customer requirements. Only under these conditions they will have a certain consumer value. At the same time, the opinions of the worker and the consumer may vary. The authors of the article set the goal to conduct a ranking of subjective consumer values that form the competitiveness of service station from the point of view of the client and from the point of view of the employee. The method of expert evaluations is chosen for the ranking. The respondents' survey has shown that both employees and consumers of service station are unanimous in their opinion about such consumer values: the quality of maintenance and repair work, the price of services, the timing of performance of orders and the external attractiveness of service station (aesthetics).